Peran Kader dalam Penurunan Stunting di Desa : The Role of Cadres in Decreasing Stunting in the Village - Kadar Ramadhan; Christina Entoh; Nurfatimah Nurfatimah (Poltekkes Kemenkes Palu, 2022)
Introduction: The government's seriousness in preventing stunting contained in the national strategy to accelerate stunting prevention should be appreciated. The inclusion of stunting as a priority problem in the use of village funds is the right step because the village is the spearhead, therefore in every village there must be health cadres who focus on this problem. Given the vital role of cadres, cadres need to be equipped with good knowledge. The purpose of this study was to increase the role of cadres in preventing stunting in Bulili Village, South Lore District. Methods: This study is a cohort study for 3 months with the target focus is posyandu cadres and the output is the nutritional status of Length for Age of all children aged 0-23 months in Bulili Village, South Lore District. Results: the results showed that the efforts of cadres succeeded in reducing the prevalence of stunting from 35.3% in November 2018 to 16.7% in October 2019, exclusive breastfeeding was associated with stunting. Conclusion: Cadre assistance must be carried out continuously so that cadre performance remains good. ABSTRAK Pendahuluan: Keseriusan pemerintah dalam pencegahan stunting yang terdapat dalam strategi nasional percepatan pencegahan stunting patut diapresiasi. Dimasukannya stunting sebagai prioritas masalah dalam penggunan dana desa merupakan langkah tepat karena desa adalah ujung tombaknya, olehnya itu di setiap desa harus ada kader kesehatan yang fokus pada masalah ini. Mengingat peran kader yang vital maka kader perlu dibekali dengan pengetahuan yang baik. Tujuan penelitian ini adalah untuk meningkatkan peran kader dalam pencegahan stunting di Desa Bulili Kecamatan Lore Selatan. Metode: Penelitian ini merupakan penelitian cohort selama 3 bulan dengan fokus sasaran adalah kader posyandu dan outputnya adalah status gizi TB/U semua anak usia 0-23 bulan di Desa Bulili Kecamatan Lore Selatan. Hasil: hasil penelitian menunjukan usaha kader berhasil menurunkan prevalensi stunting dari 35,3% pada November 2018 menjadi 16,7% pada Oktober 2019, pemberian ASI eksklusif berhubungan dengan kejadian stunting. Simpulan: Pendampingan kader harus dilakukan berkelanjutan agar kinerja kader tetap baik.